2007
DOI: 10.1016/j.actpsy.2006.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Is there a general task switching ability?

Abstract: Participants were tested on two analogous task switching paradigms involving Shape/Size tasks and Vertical/Horizontal tasks, respectively, and three measures of psychometric intelligence, tapping fluid, crystallized and perceptual speed abilities. The paradigms produced similar patterns of group mean reaction times (RTs) and the vast majority of the participants showed switching cost (switch RT minus repeat RT), mixing cost (repeat RT minus single-task RT) and congruency effects. The shared intra-individual va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
72
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 53 publications
(78 citation statements)
references
References 61 publications
5
72
1
Order By: Relevance
“…Stimulus congruency in task switching means that a certain bivalent stimulus is associated with the same response independently of in which task context it has been placed. It has been shown that congruency effects can modulate the size of the switch cost in such a way that incongruent situations produce a relatively larger switch cost (e.g., Meiran, 1996Meiran, , 2000Meiran et al, 2000;Yehene & Meiran, 2007). We would like to raise the possibility that the difference in the findings between our study and the study by Stoet et al might be generated by the congruent stimuli possibly attenuating the switch cost in the latter study.…”
Section: Discussioncontrasting
confidence: 54%
“…Stimulus congruency in task switching means that a certain bivalent stimulus is associated with the same response independently of in which task context it has been placed. It has been shown that congruency effects can modulate the size of the switch cost in such a way that incongruent situations produce a relatively larger switch cost (e.g., Meiran, 1996Meiran, , 2000Meiran et al, 2000;Yehene & Meiran, 2007). We would like to raise the possibility that the difference in the findings between our study and the study by Stoet et al might be generated by the congruent stimuli possibly attenuating the switch cost in the latter study.…”
Section: Discussioncontrasting
confidence: 54%
“…Specifically, the proportion of participants whose results fitted Model 2 in the short CTI (11 out of 31, 35%) increased relative to the results modeled earlier (Yehene & Meiran, 2007, ShapeSize results; 12 out of 95, 13%) when category-response cues were used. Concomitantly, the proportion of participants whose results fitted Model 1 (15/31 = 48%) decreased relative to the results of Yehene and Meiran (55/ 95 = 58%).…”
Section: Validation Studymentioning
confidence: 73%
“…This mathematical theory is, to the best of our knowledge, the first theory that provides a unified explanation for switching, preparation, and action-related effects on mean reaction time (RT), RT distributions and error rates. In the third part, we use CARIS to model results from an experiment comparing switching between objectbased tasks (SHAPE and SIZE) and between spatial location tasks (UP-DOWN and RIGHT-LEFT; Yehene & Meiran, 2007). The results of a study which validated the modeling conclusion follow.…”
Section: Introductionmentioning
confidence: 85%
See 2 more Smart Citations